In Vitro Release Test of Nano-drug Delivery Systems Based on Analytical and Technological Perspectives - Nemutlu, Emirhan; Eroğlu, İpek and Eroğlu, Hakan and Kır, Sedef (Current Analytical Chemistry, 2019)
Background: Nanotech products are gaining more attention depending on their advantages for improving drug solubility, maintenance of drug targeting, and attenuation of drug toxicity. In vitro release test is the critical physical parameter to determine the pharmaceutical quality of the product, to monitor formulation design and batch-to-batch variation. Methods: Spectrophotometric and chromatographic methods are mostly used in quantification studies from in vitro release test of nano-drug delivery systems. These techniques have advantages and disadvantages with respect to each other considering dynamic range, selectivity, automation, compatibility with in vitro release media and cost per sample. Results: It is very important to determine the correct kinetic profile of active pharmaceutical substances. At this point, the analytical method used for in vitro release tests has become a very critical parameter to correctly assess the profiles. In this review, we provided an overview of analytical methods applied to the in vitro release assay of various nanopharmaceuticals. Conclusion: This review presents practical direction on analytical method selection for in vitro release test on nanopharmaceuticals. Moreover, precautions on analytical method selection, optimization and validation were discussed.
Keywords: HPLC